Care of the eye during anaesthesia and intensive care. Issue 12 (December 2019) - Small, James; Robertson, Emily; Runcie, Colin
Abstract: This article describes care of the eye during a period of vulnerability in anaesthesia and intensive care. Risk factors, mechanisms of injury, recognition and management of common and important eye injuries will be covered as well as good practice points and preventative measures pertinent to all anaesthetists and critical care practitioners.